On the structure of the set of nonwandering points of a pair of coupled quadratic maps - Dobrynskii, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
In the plane of parameters, we indicate values for which plane endomorphisms constructed by coupling two identical one-dimensional unimodal quadratic maps have an absorbing domain that contains an attractor and a nontrivial invariant subset of the set of nonwandering points.